A hybrid RANS/LES approach with scale-adaptive capabilities for highly separated flows. Issue 1 (7th February 2019) - Zheng, Weilin; Xie, Fan; Yan, Chao; Zeng, Wen
ABSTRACT: A new hybrid RANS/LES approach with scale-adaptive capabilities is developed. The blending function in the SST model is adopted to prevent the invasion of the von Karman length scale to the RANS region, and the compressibility correction proposed by Wilcox is incorporated to produce a realistic shear layer development in compressible flows. The new model is validated for a subcritical flow past a circular cylinder and a supersonic base flow. Time-averaged turbulent statistics predicted by the new model show fairly good agreement with the experimental data, slight improvements over DES simulations, and are much better than SAS results. The main advantage of the new model over the DES method is that the distribution of the blending function reflects local vortex structures instead of grid spacing in the turbulent wake. The sequence of the effect intensity of the compressibility correction from strong to weak is SAS, the new model and DES.